CGIAR week of science and practice of scaling agri-food system innovation workshop report - Jacobs-Mata, Inga; Nohayi, Ngowenani; Fakudze, Bhekiwe; Nkosi, Mahlatse; Gabriel, Sherwin; Dahl, Hauke; Ires, Idil; Ermyas, Saba (CGIAR System Organization, 2022)
The Ukama Ustawi week of science and practice of scaling agri-food system innovation took place in Nairobi from 22 – 24 November 2022. More than 100 participants from CGIAR, GIZ, agribusinesses and financing platforms, public and private scaling partners, and donors attended the events.